Research progress of Traditional Chinese and Western medicine nursing for shivering during elective cesarean section (择期剖宫产术中寒战的中西医护理研究进展) - HUANG Yi (黄旖); YU Yuxiu (于玉秀); ZHONG Shaohui (钟少晖); Li Xingqing (利心情) (中西医结合护理)
shivering is one of common causes of maternal discomfort during cesarean section. This paper reviewed the studies on shivering during elective cesarean section in perspectives of its mechanism, risk factors, comprehensive heat-preservation and Traditional Chinese Medicine nursing interventions, and provided reference for prevention and control of shivering during elective cesarean section. (寒战是剖宫产手术中引起产妇不适的常见原因之一。本研究就剖宫产术中寒战发生机制、发生的危险因素、术中寒战的综合保温护理、中医特色护理干预措施进行综述, 皆在为剖宫产产妇术中寒战的防治提供可靠参考。)